INNOVATIVE APPROACHES TO MODELING BUSINESS PROCESSES OF HOTEL AND RESTAURANT ENTERPRISES - LEBEDENKO, Tetiana; POPOVA, Svitlana; NYKYFOROV, Radion; KORENETS, Yurii; SHKVARUN, Lybov (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Integration of Ukraine to the europian and world economic patterns creates hard terms for doing business domestic companies, including for the enterprises of hotel-restaurant господарстав. It requires mastering of new rules, that is dictated by a market economy, where that organization, that has the most modern technologies, top quality of products and services, most subzero prices and referencepoints on a demanding consumer, survives. Constantly to promote the level of quality and competitiveness of the products and services, enterprise force to search new, more effective methods of analysis of activity and management an enterprise.Application of процесного approach in the world is examined as a successful operating of enterprise condition, as base conception of modern management of quality. According to this approach activity of enterprise is characterized through business processes. Description of general work of enterprise and his business processes is a difficult task. Complication management business processes that exist on modern enterprises, forms objective pre-conditions for the use of modern facilities for their design that stipulates actuality of work.
Keywords: hotel economy; service; business process; functional design